Death by chocolate snickerdoodle ebook - Graves, Sarah (Death by Chocolate Mystery., 2021)
This fun new story from a rising star of culinary cozies is just what your sweet mystery tooth is craving. The Chocolate Moose Bakeshop and its irresistible pastries are as delicious and delightful as the fourth installment in the Death By Chocolate series by Sarah Graves. As co-owners of Eastport's beloved waterfront bakery, the Chocolate Moose, Jake and Ellie know their customers expect them to cream the competition at the town's annual Cookie Baking Contest. But they're really just in it for fun, hoping to get Jake's daughter-in-law baking again. Those plans collapse when fearsome local curmudgeon Alvin Carter is murdered, and every crumb of evidence points to Tiptree family friend—and all-around sweet guy—Billy Breyer. Billy's sisters beg Jake and Ellie to prove his innocence. After all, lots of folks had gone sour on Alvin, whose popularity ranked somewhere between a toothache and the plague. But just as the ladies begin sifting through the suspects, a series of grass fires blaze across the island, threatening catastrophe. Now, Jake and Ellie will need all their courage—and an extra dash of that downeast Maine stubbornness—to sniff out the real killer before anyone else gets burned . . . Includes a Recipe! " A treat for aficionados of shopkeeper-sleuth cozies." —Kirkus Reviews "Entertaining. . . . Cozy fans are sure to have fun." — Publishers Weekly